Optimizing information and communication technology applications in chemistry learning - Nwafor, Stephen Chinedu; Ibe, Franklin Nnanna; Muoneke, Nneora Mary (Univeritas Papua, 2022)
Information and communication technology (ICT) is crucial to the educational growth of any country and the academic interactions and collaborations of students. The study determined the extent of ICT application in chemistry instruction in Anambra State, Nigeria, secondary schools. This study uses a descriptive survey. A total of 133 students and 12 chemistry teachers as samples. The t-test was used to test the research hypothesis. The study's findings revealed a low extent of ICT application in teaching and learning chemistry in Anambra State, Nigeria. Moreover, both the chemistry teachers and students agree that ICT is applied to a low extent for teaching and learning chemistry in Anambra State, Nigeria. The study also revealed that the use of outdated computers; lack of technical assistance; lack of time; lack of computer hardware/software; lack of electricity; broken down computers; lack of internet or slow connectivity, and high cost of computers are some of the challenges of ICT application while the provision/maintenance of adequate ICT software and hardware, exposure of chemistry teachers to workshops and conferences and provision of uninterrupted internet services and power supply by the government among others were proffered as possible strategies to eliminate these challenges.